2021
DOI: 10.4235/agmr.21.0082
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in Frail Older Adults

Abstract: Delirium and frailty are prevalent geriatric syndromes and significant public health issues among older adults. The prevalence of delirium among hospitalized older adults can be from 15% to 75%, and the prevalence of frailty ranges between 12% and 24%. The exact pathophysiology of these two conditions is not clearly identified, and there are several hypotheses. But it is thought that they are multifactorial in their etiology and are associated with inflammation related to aging, alteration of vascular systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 86 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…Delirium and frailty, especially in advanced stages marked by functional disability, exhibit a mutually independent relationship, as demonstrated by the results of a meta‐analysis by Perisco et al, which reported that patients afflicted with frailty faced a 2.2‐fold heightened risk of developing delirium 32 . These conditions are multifactorial in etiology, sharing common underlying factors, such as age‐related inflammation, vascular alterations, nutritional deficiencies, and multimorbidity 33 . Delirium prevention assumes paramount importance, as pharmacological interventions are often associated with significant adverse effects, 34 whereas nonpharmacological interventions are frequently rendered ineffective once the complication has manifested 35 …”
Section: Discussionmentioning
confidence: 99%
“…Delirium and frailty, especially in advanced stages marked by functional disability, exhibit a mutually independent relationship, as demonstrated by the results of a meta‐analysis by Perisco et al, which reported that patients afflicted with frailty faced a 2.2‐fold heightened risk of developing delirium 32 . These conditions are multifactorial in etiology, sharing common underlying factors, such as age‐related inflammation, vascular alterations, nutritional deficiencies, and multimorbidity 33 . Delirium prevention assumes paramount importance, as pharmacological interventions are often associated with significant adverse effects, 34 whereas nonpharmacological interventions are frequently rendered ineffective once the complication has manifested 35 …”
Section: Discussionmentioning
confidence: 99%
“…A study of 2,065 patients aged 65 years or older hospitalized in 118 acute medical wards and 46 rehabilitation units in Italy found that there was no interaction between delirium and frailty on 30-day mortality (P = 0.477) [32]. The discrepant findings between studies may relate in part to variations in study populations, sample size, and tools for the assessment of frailty and delirium [6,33].…”
Section: Discussionmentioning
confidence: 99%
“…Growing knowledge on the importance of the frailty spectrum might be one of the most remarkable achievements in geriatric medicine in this century in person-centered risk assessment and care provision for older adults (4)(5)(6). Measured by either the phenotype or the index, the spectrum of frailty has shown high prediction ability for adverse health outcomes encompassing healthcare use and incidence of geriatric syndromes, such as fall and delirium, as well as disability and death (7,8). These features of frailty have led to a growing research interest in incorporating frailty as a risk measure in many specialized fields of medicine outside geriatrics (9).…”
Section: Introductionmentioning
confidence: 99%